Impacto de la educación virtual en los docentes de básica superior en la Escuela de Educación Básica General Quisquís periodo lectivo 2020 – 2021 - Granizo Delgado, Yuri Galager (2021)
Teachers in Ecuador and around the world have had to modify their classes to virtual mode from the suspension of face-to-face classes due to the COVID-19 pandemic. The objective of this study is to determine the Impact of virtual education on teachers of higher basic education in the general basic education school "QUISQUÍS" school period 2020-2021. This study used a qualitative approach based on a survey composed of 8 questions applied to 5 teachers of Basic Education at the upper sub-level. As a result, it is obtained that not all teachers were prepared for this change of modality, due to the little mastery of virtual platforms, reason to keep them in fear and uncertainty most of the time dedicated to their work; However, they remain optimistic and with a great learning predisposition to improve their skills and abilities that lead them to strengthen their teaching work. It is required that they be given greater support and technological training to mitigate fears and facilitate the mastery of technology that allows them to function adequately in the virtual modality.